Samples of Kalmyk Buddhist literature in I. I. Popov’s materials - S. V. Mirzaeva (Nomadic Civilization: Historical Research)
Buddhist translated texts form a significant part of written heritage of Mongolian peoples, in particular Kalmyks, and are represented in handwritten materials of I. I. Popov, the collector of Kalmyk folklore of the turn of 19th–20th centuries. The paper aims to give description and analysis of Buddhist sutras and samples of narrative literature which were written down by I. I. Popov and preserved in one of his manuscripts entitled as “Translations of various texts from Kalmyk to Russian made by I. I. Popov”. The analysis of the manuscript gives opportunity to define most popular and wide-spread sacred Buddhist texts — “Diamond sutra”, “Sutra of Amitabha”, “Sutra of White Old-man” and other canonical and apocryphal works. Of great interest, in our opinion, are author’s foreword and small introductions to great part of texts because they contain valuable data on informants recorded by I. I. Popov.